2006
DOI: 10.1080/08035250500297810
|View full text |Cite
|
Sign up to set email alerts
|

8-hydroxy-2-desoxyguanosine serum concentrations as a marker of DNA damage in patients with classical galactosaemia

Abstract: a) Low TAS and high Gal-1-P levels are implicated with high 8-OHdG blood levels in galactosaemic patients; b) 8-OHdG may be a sensitive biomarker of DNA damage in patients with classical galactosaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…That said, anecdotal studies have shown that galactosemic patients on poor dietary control display increased markers of oxidative stress yet lower total antioxidant status (Schulpis et al, 2005; Schulpis et al, 2006). Considering that antioxidant supplements (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That said, anecdotal studies have shown that galactosemic patients on poor dietary control display increased markers of oxidative stress yet lower total antioxidant status (Schulpis et al, 2005; Schulpis et al, 2006). Considering that antioxidant supplements (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, despite heightened oxidative stress biomarkers, galactose-treated rodents, flies and tissue culture cells also demonstrated evidence of lower than expected antioxidant enzyme activities (Cui et al, 2004; Cui et al, 2006), suggesting that the normal defences might be compromised; no mechanism has yet been established. Of note, anecdotal studies have shown that galactosemic patients on poor dietary control also displayed lower total antioxidant status along with remarkably increased markers of oxidative stress (Schulpis et al, 2005; Schulpis et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the etiology of the disease is still poorly understood [9,10]. Patients with classical galactosemia present alteration in markers of oxidative stress and in activities of Na + , K + -ATPase, and Mg 2+ -ATPase in blood [11,12]. The treatment of patients' fibroblasts with GAL alters calcium homeostasis and causes reticular stress [13].…”
Section: Introductionmentioning
confidence: 99%
“…41 with moderate or very restricted diet. 64 In addition, experiments in rats fed with high dose of galactose showed the increase of lipid peroxidation and a decrease of antioxidant enzymes such as superoxide dismutase (SOD) and catalase in their brain. 41,65 Experiments in Drosophila showed an increase in oxidative stress and decrease in antioxidant defences after galactose treatment compared to control.…”
Section: Pseudotumor Cerebri and Cataractsmentioning
confidence: 99%